2007
DOI: 10.1007/s00423-007-0206-1
|View full text |Cite
|
Sign up to set email alerts
|

Is palliative resection necessary for gastric carcinoma patients?

Abstract: The results highlight the improved survivorship of gastric carcinoma patients with palliative resection compared to those who did not undergo the procedure. Although curative resection is not possible in this group of patients, we recommend performing resection aimed at palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…Based on the survival benefits, feasibility of non-curative gastrectomy for single organ metastasis, distant lymph node metastasis was generally accepted by many authors [10], [38]. Evidence existed of improved survival by non-curative gastrectomy in peritoneal metastatic disease, with the median OS ranging from 5 to 21.7 months [9], [38], [40][43]. However, the opposite evidence of gastrectomy or bypass in peritoneal metastasis also existed [10], [44] and authors failed to build consensus on the feasibility of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the survival benefits, feasibility of non-curative gastrectomy for single organ metastasis, distant lymph node metastasis was generally accepted by many authors [10], [38]. Evidence existed of improved survival by non-curative gastrectomy in peritoneal metastatic disease, with the median OS ranging from 5 to 21.7 months [9], [38], [40][43]. However, the opposite evidence of gastrectomy or bypass in peritoneal metastasis also existed [10], [44] and authors failed to build consensus on the feasibility of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Localization of the tumor in the stomach did not affect the survival [2,3]. Although the size of the tumor is considered as an important parameter in the study of Kunisaki et al [2], neither present study nor the study of Kim et al [11] supports this finding.…”
Section: Discussionmentioning
confidence: 51%
“…Neither in this study nor in the others, the age of the patient was determined as a factor that significantly affects survival [2,3,11]. On the other hand, Hartgrink et al [1] indicated that resection was not effective in patients who are older than 70 years of age with multiple metastases.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations